Analisa unjuk kerja alat pembagi tekan pada pompa hydram - Wardani, K. (Universitas Mataram, 2019)
Water is source of life for human being, plant and animal. One of effort to complete of water required is by using hydram pump. Hydram pump (Hydraulic ram pump) is a pump that work without required energy from outside for its activated, but work done by exploiting force from source of water. This research purposes to know influence of pressure divisor to water hammer effect and to know influence of pressure divisor to efficiency of hydram pump. This research used hydram pump by the specification of air tube it’s 60 cm height and 3 inches diameter. Elevation of plunge from pump body is 2 meters and elevation of output is 4 meters. Height of air tube at pressure divisor that is 20 cm, 30 cm, 40 cm and 50 cm and elevation of variaty pressure divisor from body pump is 2 meters, 2,5 meters and 3 meters. The method used in this research is experiment method. The quantitative data made in table and displayed graphically. The results show that the highest of maximum head at 2 meters elevation of pressure divisor from pump body and 20 cm high of tube, while lowest of maximum head at 3 meters elevation of pressure divisor from pump body and 50 cm high of tube. The best efficiency at 2 meters elevation of pressure divisor from pump body and 20 cm high of tube that is 31,62%, while the lowest efficiency at hydram pump installation without of pressure divisor that is only 26,62%.